Original and introduced lineages co-driving the persistence of Brucella abortus circulating in West Africa - Liu, Zhiguo; Wang, Miao; Shi, Qi; Dong, Xiaoping; Gao, Liping; Li, Zhenjun (Frontiers in Public Health, 2023)
Brucellosis, a serious public health issue affecting animals and humans, is neglected in West Africa (WA). In the present study, bio-typing, multi-locus sequence typing (MLST), multiple-locus variable-number tandem repeat analysis (MLVA), and whole genome sequencing single-nucleotide polymorphism (WGS-SNP) analysis were used to characterize the Brucella abortus (B. abortus) strains from WA. All of the 309 strains analyzed in this study were extracted and downloaded from the international MLVA bank and were from 10 hosts (cattle, humans, ovine, buffalo, dromedaries, horse, sheep, zebu, dog, and cat) distributed in 17 countries in WA. Based on the bio-typing, three biovars, dominated by B. abortus bv.3, were observed and reported across seven decades (1958–2019). With MLST, 129 B. abortus strains from the present study were sorted into 14 STs, with ST34 as the predicted founder. These 14 STs clustered into the global MLST data into three clone complexes (CI-CIII) with the majority of strains clustering in CI, while CII forms an independent branch, and CIII harbors three STs shared by different continents. These data revealed that most cases were caused by strains from native lineages. According to the MLVA-11 comparison, 309 strains were divided into 22 MLVA-11 genotypes, 15 of which were unique to WA and the remaining seven had a global distribution. MLVA-16 analysis showed that there were no epidemiological links among these strains. Based on the MLVA data, B. abortus strains from WA have high genetic diversity, and predominated genotypes were descended from a native lineage. While the MLVA-16 globally highlights that the dominant native and few introduced lineages (from Brazil, the USA, South Korea, Argentina, India, Italy, Portugal, the UK, Costa Rica, and China) co-driving the B. abortus ongoing prevalence in WA. The high-resolution SNP analysis implied the existence of introduced B. abortus lineages, which may be reasonably explained by the movement and trade of dominant hosts (cattle) and/or their products. Our results indicated that B. abortus strains in WA consist of native and introduced strains that necessitate control such as vaccination, testing, slaughtering, and movement control by the relevant country authorities to reduce brucellosis in livestock.